2021
DOI: 10.35848/1882-0786/ac200b
|View full text |Cite
|
Sign up to set email alerts
|

Low-threshold-current (~85 mA) of AlGaN-based UV-B laser diode with refractive-index waveguide structure

Abstract: We report on a refractive-index waveguide AlGaN-based ultraviolet-B band (UV-B) laser diode grown on a sapphire substrate, which achieves a laser oscillation at a low threshold current (I th ), ∼85 mA. The refractive index waveguide structure in a ridge-type structure is fabricated by a unique method combining dry inductively coupled plasma reactive ion etching and wet etching with tetramethylammonium hydroxide solution. Using this structure, the longitudinal-mode transverse optical confinement is successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Notably, the LDs with a threshold current density (J th ) below 10 kA cm −2 have also been reported, in which a refractiveindex waveguide laser structure was employed. 12,13) Two breakthrough technologies have made the realization of DUV LDs possible: (i) the polarization doping 14,15) in the p-type cladding layer of both UV-B and UV-C LDs enables the high current density operation and the favorable optical cavity formation. 16) (ii) The achievement of high-quality AlGaN crystals with low carrier injection and high optical gain.…”
mentioning
confidence: 99%
“…Notably, the LDs with a threshold current density (J th ) below 10 kA cm −2 have also been reported, in which a refractiveindex waveguide laser structure was employed. 12,13) Two breakthrough technologies have made the realization of DUV LDs possible: (i) the polarization doping 14,15) in the p-type cladding layer of both UV-B and UV-C LDs enables the high current density operation and the favorable optical cavity formation. 16) (ii) The achievement of high-quality AlGaN crystals with low carrier injection and high optical gain.…”
mentioning
confidence: 99%
“…The threshold currents are 1300 and 1250 mA, respectively, which correspond to the estimated J th values of 26 and 25 kA cm −2 . Compared with the lowest LD J th values reported so far, [ 21,23,29 ] the current values were almost twice as high; thus, we conducted TEM experiments on the device fabricated using the AlN nanopillar method, and the results indicated that the thickness of the quantum wells in the active layer decreased from 4 to 2.5 nm. [ 25 ] This is presumably due to changes in the growth rate of the well layer over time, which is caused by the changes in the reaction conditions of the metal organic vapor phase epitaxy system.…”
Section: Methodsmentioning
confidence: 91%
“…Double sputtering and thermal cycle HTA were further proposed, and the TDD of Al-polar AlN film on sapphire was reduced to 2.4 × 10 7 cm –2 , which is the best result reported so far. Room-temperature lasing of AlGaN-based UVB LDs grown on annealed sputtered AlN templates have been demonstrated . Brunner et al found that pits on Al-polar AlN films on SiC were eliminated from the surface after HTA, and the edge dislocation density was reduced from 1 × 10 10 to 1 × 10 9 cm –2 .…”
Section: Introductionmentioning
confidence: 99%
“…Room-temperature lasing of AlGaN-based UVB LDs grown on annealed sputtered AlN templates have been demonstrated. 23 Brunner et al found that pits on Al-polar AlN films on SiC were eliminated from the surface after HTA, and the edge dislocation density was reduced from 1 × 10 10 to 1 × 10 9 cm −2 . 24 However, the polarity of AlN films in those studies was Al-polar or not explicitly claimed.…”
Section: ■ Introductionmentioning
confidence: 99%